Velvet ants of the tribe Smicromyrmini Bischoff (Hymenoptera: Mutillidae)of Japan - Okayasu, Juriya (Zootaxa, 2020)
Japanese species and genera of the tribe Smicromyrmini Bischoff, 1920 are revised. Most of the relevant types were examined. The following eight species in the genera Smicromyrme Thomson, 1870, Nemka Lelej, 1985, Mickelomyrme Lelej, 1995, Andreimyrme Lelej, 1995, Ephucilla Lelej, 1995 and Sinotilla Lelej, 1995 are recognized from Japan: Sm. lewisi Mickel, 1935, ♂♀; N. yasumatsui (Mickel, 1936), stat. rev. et comb. nov., ♂♀; M. hageni (Zavattari, 1913), ♂♀; A. substriolata (Chen, 1957), ♀ (Amami-ôshima Is., Okinawa-jima Is.); E. yoshitakei sp. nov., ♂♀ (Amami-ôshima Is.), E. suginoi sp. nov., ♂♀ (Okinawa-jima Is.), E. brevitegula sp. nov., ♂♀ (Ishigaki-jima Is., Iriomote-jima Is.); Si. jambar sp. nov., ♂ (Okinawa-jima Is.). The genera Andreimyrme and Sinotilla are newly recorded from Japan. Nemka wotani (Zavattari, 1913) and Ephucilla naja (Zavattari, 1913) are excluded from the Japanese fauna. New synonymies are proposed for N. wotani (Zavattari, 1913) [=Smicromyrme chihpenchia Tsuneki, 1993, syn. nov.], N. limi limi (Chen, 1957) [=Smicromyrme limi nanhai Chen, 1957, syn. nov.], A. substriolata [=Smicromyrme tridentiens Chen, 1957, syn. nov.] and Neotrogaspidia pustulata (Smith, 1873) [=Smicromyrme yakushimensis Yasumatsu, 1934, syn. nov.]. Phimenes flavopictus formosanus (Zimmermann, 1931) (Hymenoptera: Vespidae: Eumeninae) is recorded as a host of Ephucilla brevitegula. Other new records include: Mickelomyrme athalia (Pagden, 1934) from China (Guangdong, Fujian, Yunnan) and Vietnam (Hoa Binh), M. bakeri (Mickel, 1934) from Malaysia (Borneo) and Indonesia (Sulawesi), M. pusillaeformis (Hammer, 1962) from Indonesia (Bali), Andreimyrme sarawakensis Lelej, 1996 from Peninsular Malaysia (Kuala Lumpur) and A. substriolata from Laos (Xiengkhouang, Houapanh), Thailand (Chiang Mai), Peninsular Malaysia (Kuala Terengganu) and Indonesia (Sumatra). Distributions of Japanese smicromyrmine species are classified into the following three patterns: Asian continental-Palaearctic Japan (Sm. lewisi and N. yasumatsui), Taiwan-Ryûkyû (M. hageni, E. yoshitakei, E. suginoi, E. brevitegula, Si. jambar) and Asian continental-Ryûkyû (A. substriolata). Species of Asian continental-Palaearctic Japan are widely distributed in Palaearctic part of Japan and eastern part of Eurasia, or have the closest relative in continental Asia. They are considered to be native to Japan since it was a part of Eurasia, or have immigrated to Japan through the land bridge between Korean Peninsula and Japan by the end of the Upper Pleistocene. The Taiwan-Ryûkyû species are immigrants from Taiwan through the land bridge. The Asian continental-Ryûkyû species is presumed to have immigrated to Japan during the Upper Pleistocene when the eastern edge of Eurasian Continent was close to Amami-ôshima Is.